Making habeas work : a legal history - Freedman, Eric M. (New York : New York University Press, 2019)
Habeas corpus, known as the Great Writ of Liberty, is a judicial order that requires government officials to produce a prisoner in court, persuade an independent judge of the correctness of their claimed factual and legal justifications for the individual's imprisonment, or else release the captive. Frequently the officials resist being called to account. Much of the history of the rule of law, including the history being made today, has emerged from the resulting clashes. This text, heavily based on primary sources from the colonial period and the early national period and significant research in the New Hampshire State Archives, seeks to illuminate the past and draw lessons for the present.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 30, 2018).
Keywords: Habeas corpus -- United States -- History; Habeas corpus -- England -- History; Law; Laws of specific jurisdictions & specific areas of law